Cellular actuators : modularity and variability in muscle-inspired actuation - Ueda, Jun (Professor of mechanical engineering) (Butterworth-Heinemann, 2017)
Cellular actuators: modularity and variability in muscle-inspired actuation describes the roles actuators play in robotics and their insufficiency in emerging new robotic applications, such as wearable devices and human co-working robots where compactness and compliance are important. Piezoelectric actuators, the topic of this book, provide advantages like displacement scale, force, reliability, and compactness, and rely on material properties to provide displacement and force as reactions to electric stimulation. The authors, renowned researchers in the area, present the fundamentals of muscle-like movement and a system-wide study that includes the design, analysis, and control of biologically inspired actuators.